THE EFFECT OF LEARNING STRATEGY AND COGNITIVE STYLE ON STUDENTS’ NARRATIVE WRITING ABILITY - Tata Tambi; Fathiaty Murtadho; Aceng Rahmat (University of Kuningan, 2022)
In the class, most of the teacher use a single teaching strategy to students who have different cognitive styles when teaching narrative essays in the class. Therefore, it is necessary to improve teaching strategies in the teaching and learning process. The teaching strategies that fit with the cognitive style of students in order that the learning objective is improved. This paper investigates the effect of learning strategy and cognitive style on student’s narrative writing ability. This study was conducted on the VII grade students at Madrasah Tsanawiyah Ibnu Taimiyah Bogor, West Java. Treatment by level design and two-factorial ANOVA analysis with α = 0.05 were applied in this experimental study. The sample was 40 students grouped into experiment classes and 40 students was grouped into control classes. There was a different ability in narrative writing in Bahasa Indonesia between students having field independent cognitive style (A1) and students having field dependent cognitive style (A2). Results of two-way interrow analysis of variance showed that Fcalculated (4.123) was higher than Ftable (3.97) at a significant level of α = 0.05. The findings showed the ability to write a narrative writing in Bahasa Indonesia of students having a field independent cognitive style was higher than that of students having a field dependent cognitive style.